3D micro-nanostructure based waterproof triboelectric nanogenerator as an outdoor adventure power source. (September 2022) - Sun, Yue; Zheng, Yide; Wang, Run; Lei, Tongda; Liu, Jian; Fan, Jie; Shou, Wan; Liu, Yong
Abstract: Triboelectric nanogenerators (TENGs) have attracted wide attention in recent years for powering wearable electronics. However, the electrical output of TENGs is severely affected in high-humidity environments, which greatly limits their applications. Herein, we reported a waterproof, humidity-resistant TENG consisting of three-dimensional (3D) micro-structured polydimethylsiloxane (PDMS) film and polyacrylonitrile (PAN) nanofiber/zinc oxide nanorods (ZnO NRs) composite membranes triboelectric material. Hereafter, we call it 3D PDMS-ZnO/PAN TENG. The introduction of ZnO NRs on PAN nanofiber and 3D structured PDMS significantly enhances the electrical output of the fully packaged TENG, offering a maximum power density of 184.6 μW/cm 2 . Under the impact force of 30 N at 2 Hz frequency, the fabricated TENG can generate voltage and current of approximately 166 V and 37 μA. In addition, the TENG also exhibits an excellent electrical output performance at high humidity (up to 92 % RH) and even inside water. We further show that our TENG can work as a sustainable power source to drive commercial light-emitting diodes (LEDs), calculator, and hygrothermograph. Given its excellent electrical output performance in water and humid conditions, the TENG has a great potential for powering outdoor electronics in extreme weather. Graphical Abstract: ga1 Highlights: A novel 3D Micro-nanostructured TENG is proposed to harvest energy at high humidity or even in water. The growth of ZnO NRs not only improves the surface roughness but also the tribopositivity of the nanofiber membrane. The TENG realizes the contact-separation without any spacer through the 3D pillar structure. The TENG exhibits excellent electrical output performance in a water environment.